Crystal structure of (E)-dichloro(1-chloro-3-methoxyprop-1-en-2-yl)(4-methoxyphenyl)-λ4-tellane, C11H13Cl3O2Te - Caracelli, Ignez; Zukerman-Schpector, Julio; Cunha, Rodrigo L.O.R.; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C11H13Cl3O2Te, monoclinic, P21/c (no. 14), a = 11.0098(8) Å, b = 16.471(1) Å, c = 8.4975(7) Å, β = 99.421(7)°, V = 1520.17(19) Å3, Z = 4, Rgt(F) = 0.0306, wRref(F2) = 0.0852, T = 293(2) K.